Juvenile Justice in Comparative Perspective: A Study of Indonesian State Law and Islamic Law - Hadiputra, Adrian; Maskur, Muhammad Azil; Arifin, Ridwan; Amrullah, Ikram; Maajid, Hibatullah (Faculty of Law, Universitas Negeri Semarang, 2024)
This study examines juvenile justice systems through a comparative analysis between Indonesian State Law and Islamic Law, focusing on the treatment and legal protection of juvenile offenders. The Indonesian legal framework, which follows a secular approach, offers specific regulations for juvenile justice under the Juvenile Justice System Law (No. 11 of 2012). This law emphasizes rehabilitation and diversion, ensuring that juvenile offenders are treated differently from adults, with a focus on reintegration into society. In contrast, Islamic law, rooted in the principles of Sharia, offers a distinct approach to juvenile justice. While Islamic law does not have a unified legal code for juvenile offenders, its application emphasizes the protection of minors from harsh punishments and prioritizes their rehabilitation. Islamic legal scholars agree on the importance of age and maturity in determining the level of responsibility for a juvenile’s actions. The concept of